1985
DOI: 10.1007/bf02013597
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay for detection of antibodies toPseudomonas aeruginosa exoproteins

Abstract: Enzyme-linked immunosorbent assays were developed with four purified Pseudomonas aeruginosa extracellular proteins (exotoxin A, elastase, alkaline protease, and phospholipase C) to determine antibody levels in sera from healthy subjects and the serological response in patients colonized or infected with Pseudomonas aeruginosa. Five of 39 burn patients with wounds colonized by Pseudomonas aeruginosa had elevated antibody titers to alkaline protease. Response to the other antigens was found in only a few patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA). Immunlon II polystyrene microplates (Dynatech Laboratories Inc., Alexandria, Va.) were coated overnight at 22°C with, per well, 100 ,ul of exotoxin A (2 ,ug/ml), elastase (2 pug/ml), alkaline protease (10 ,ug/ml), phospholipase C (10 p.g/ml), or LPS (10 jig/ml) in 0.02 M phosphate-buffered saline with 0.02% (wt/vol) sodium azide, pH 7.2, as previously described (16,36) with minor modifications in the antigen concentrations. Nunc immunoplates (Nunc, Thousand Oaks, Calif.) were coated with, per well, 100 RI of flagella (1 ,ug/ml) in 0.05 M carbonate coating buffer with 0.02% sodium azide, pH 9.6, as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA). Immunlon II polystyrene microplates (Dynatech Laboratories Inc., Alexandria, Va.) were coated overnight at 22°C with, per well, 100 ,ul of exotoxin A (2 ,ug/ml), elastase (2 pug/ml), alkaline protease (10 ,ug/ml), phospholipase C (10 p.g/ml), or LPS (10 jig/ml) in 0.02 M phosphate-buffered saline with 0.02% (wt/vol) sodium azide, pH 7.2, as previously described (16,36) with minor modifications in the antigen concentrations. Nunc immunoplates (Nunc, Thousand Oaks, Calif.) were coated with, per well, 100 RI of flagella (1 ,ug/ml) in 0.05 M carbonate coating buffer with 0.02% sodium azide, pH 9.6, as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…Increased antibody levels to exotoxin A or phosphatase C were observed in 15 of 22 patients with P. aeruginosa septicemia, otitis, and pneumonia. In an examination of 112 serum samples from healthy subjects of different age groups (0–3, 4–15, 16–75 years old), Granstom et al [43]showed that antibodies (IgG) to alkaline phosphatase and phospholipase C significantly increased in older children and adults. However, antibody levels to elastase and exotoxin A were not increased.…”
Section: Antigenic Properties Of Exoproductsmentioning
confidence: 99%
“…Antigenic properties of exoproducts P. aeruginosa produces a number of secreted virulence factors including exotoxin A, exoenzyme S, proteases I (neutral protease) and III (alkaline phosphatase), elastase, hemolysins (thermolabile phosphatase C and thermostable acid glycolipid), enter- Table 1 Probable role of extracellular products of P. aeruginosa in virulence and immunogenicity Extracellular antigen Role in virulence Antibody or protective response Reference Proteases : (i) Elastase Induces hemorrhagic lesions and necrosis, Abs in patients with chronic and/or active [18^20] tissue invasion, destruction of host defenses, P. aeruginosa infections; provide protections against e.g. complements and opsonins severe lung lesions in animal models (ii) Alkaline protease Destruction of non-speci¢c host defenses, Abs detected in burn wound patients [21] tissue invasion Phospholipase C Destruction of pulmonary surfactant Rise in Ab titer in CF patients colonized with [22,23] Generation of in£ammatory mediators P. aeruginosa, and in animal model infections Rhamnolipids…”
Section: Introductionmentioning
confidence: 99%
“…Increased antibody levels to exotoxin A or phosphatase C were observed in 15 of 22 patients with P. aeruginosa septicemia, otitis, and pneumonia. In an examination of 112 serum samples from healthy subjects of di¡erent age groups (0^3, 4^15, 16^75 years old), Granstom et al [43] showed that antibodies (IgG) to alkaline phosphatase and phospholipase C signi¢-cantly increased in older children and adults. However, antibody levels to elastase and exotoxin A were not increased.…”
Section: Extracellular Antigenmentioning
confidence: 99%
See 1 more Smart Citation